Reinforcement religious moderation through entrepreneurship in islamic boarding school as social empowerment function - Sarji Sarji (IAIN Salatiga, 2020)
This study aimed to explain the importance of enhancement religious moderation in Islamic boarding schools in the province of Special Capital Region of Jakarta. Then, it used to analyze the escalation in entrepreneurship and religious moderation. Furthermore, it expected could describe religious moderation and entrepreneurship as instruments of social empowerment. The method used in this research is a case study which intended to capture the phenomenon of religious moderation in Islamic boarding schools in this province through observational data, expert statements, interview’s results and document study descriptions. The outcome found in this research that religious moderation can be enhanced by religious knowledge and preserve religious emotions. In addition, entrepreneurship training include business ethics content that could encourages students to connect with various backgrounds of people who require an understanding of moderation. Additionally, the entrepreneurship program can be used as a social engineering devices for Islamic boarding schools to empower people.